Nerve Ultrasound in Peripheral Neuropathies: A Review - Kerasnoudis, Antonios; Tsivgoulis, Georgios (Journal of neuroimaging, 2015)
ΑBSTRACT Peripheral neuropathies are one of the most common reasons for seeking neurological care in everyday practice. Electrophysiological studies remain fundamental for the diagnosis and etiological classification of peripheral nerve impairment. The recent technological development though of high resolution ultrasound has allowed the clinician to obtain detailed structural images of peripheral nerves. Nerve ultrasound mainly focuses on the evaluation of the cross sectional area, cross sectional area variability along the anatomical course, echogenity, vascularity and mobility of the peripheral nerves. An increase of the cross sectional area, hypervascularity, disturbed fascicular echostructure and reduced nerve mobility are some of the most common findings of entrapments neuropathies, such as the carpal or cubital tunnel syndrome. Both the cross‐sectional area increase and the hypervascularity detected with the Doppler technique seem to correlate significantly with the clinical and electrophysiological severity of the later mononeuropathies. Significantly greater cross sectional area values of the clinically affected cervical nerve root are often detected in cases of cervical radiculopathy. In such cases, the ultrasound findings seem also to correlate significantly with disease duration. On the other hand, multifocal cross sectional area enlargement of cervical roots and/or peripheral nerves is often documented in cases of immune‐mediated neuropathies. None of the later pathological ultrasound findings seem to correlate significantly with the electrophysiological parameters or the functional disability. The aim of this review is to provide a timely update on the role of neuromuscular ultrasound in the diagnostic of the most common entrapment and immune‐mediated peripheral neuropathies in clinical practice.